2020
DOI: 10.1002/aqc.3305
|View full text |Cite
|
Sign up to set email alerts
|

Coastal breeding aggregations of threatened stingrays and guitarfish in the Levant

Abstract: Stingrays and guitarfish are globally threatened by overexploitation, particularly so in the Mediterranean Sea. Nevertheless, very little information is known about their ecology, behaviour, and taxonomy in the Mediterranean, and especially in the Levant, where water temperature, salinity, and the impact of invasive species are relatively high. Although it has been suggested that some species may aggregate in the Levant, this has not been formally documented and the scale of this phenomenon, the taxonomic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Our data also confirm the findings of [49], who suggested that Cyprus should be considered a crucial area for the conservation of G. cemiculus, a species listed as critically endangered by the IUCN Red List and whose populations have drastically decreased all along the African coastline due to overfishing [51]. In addition to Cyprus, this taxon now only survives in few locations in the Mediterranean Sea, namely, the Gulf of Gabes [52], the Israel coast [53], and Iskenderun Bay [54]. In addition, we recorded a pregnant G. cemiculus, suggesting that members of this species nurse and potentially spawn in Cyprus; a specimen of A. bovinus observed on different days in Akrotiri Bay (south coast of Cyprus), suggesting site fidelity by this species; migration routes by M. mobular, with aggregations of large specimens occurring in late winter-early spring; and in general, spawning aggregations of stingrays (Dasyatis pastinaca and Bathytoshia lata), with pregnant females observed during spring and summer seasons.…”
Section: Discussionsupporting
confidence: 86%
“…Our data also confirm the findings of [49], who suggested that Cyprus should be considered a crucial area for the conservation of G. cemiculus, a species listed as critically endangered by the IUCN Red List and whose populations have drastically decreased all along the African coastline due to overfishing [51]. In addition to Cyprus, this taxon now only survives in few locations in the Mediterranean Sea, namely, the Gulf of Gabes [52], the Israel coast [53], and Iskenderun Bay [54]. In addition, we recorded a pregnant G. cemiculus, suggesting that members of this species nurse and potentially spawn in Cyprus; a specimen of A. bovinus observed on different days in Akrotiri Bay (south coast of Cyprus), suggesting site fidelity by this species; migration routes by M. mobular, with aggregations of large specimens occurring in late winter-early spring; and in general, spawning aggregations of stingrays (Dasyatis pastinaca and Bathytoshia lata), with pregnant females observed during spring and summer seasons.…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, LEK suggests the occurrence of such aggregations in 4 GSAs (6,9,11,16), in close correspondence with the main Mediterranean distribution of the species (Follesa et al, 2020). Among Mediterranean batoids, aggregation records have been published only for D. pastinaca in the Levantine Sea (GSA 27) (Chaikin et al, 2020), but this species occurrence has been documented in other coastal areas of the central Mediterranean Sea (GSA 16, Tiralongo et al, 2020). This study highlighted two more GSAs (11 and 17) where D. pastinaca aggregations occur according to LEK.…”
Section: Aggregation -Demersal Speciesmentioning
confidence: 64%
“…Additionally, the incorporation of specific information on these aspects is essential for developing appropriate and effective management strategies (Jacoby et al, 2012;Chapman et al 2015;Braccini et al, 2016). While several studies in the Atlantic and Pacific Oceans have been performed on the social behaviours, movements and migration of elasmobranchs (see, for review, Jacoby et al, 2012;Braccini et al, 2016), very little information is currently available in the Mediterranean Sea (Abudaya et al, 2018;Barash et al, 2018;Chaikin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal changes in elasmobranch abundance have been linked to reproductive behaviour, ontogenetic habitat shifts and changing abundances of prey and predator species (Chaikin et al 2020;Le Port et al 2012;Schlaff et al 2014). Megatrygon microps and T. meyeni, although sighted throughout the year, peak in abundance in opposite seasons, when they can be seen in groups of up to four and five individuals respectively.…”
Section: Discussionmentioning
confidence: 99%